ROLE OF PHARMA DIGITALIZATION IN HEALTHCARE DEVELOPMENTS - KUMAR, SANKET; CHOUDHARY, DEEPAK (International Journal of Current Pharmaceutical Research, 2023)
Healthcare development is a revolutionary sector where digital technologies drive success, with exponential growth seen in a computing system involving advancements in medical devices. Due to social distancing norms, widespread lockdowns, and an emphasis on individualized healthcare, the Covid-19 pandemic has inevitably increased the usage of digital technologies. “Digital” has become the most essential part of day-to-day existence, and all sectors are adapting more swiftly to the digital world. The healthcare system is more complicated, as its culture and structure are not ready to accept innovation, since development in healthcare involves decision on a person’s life or death. The use of digital health tools has the potential to significantly improve individual patient care by enhancing the accuracy diagnosis and treatment of diseases. For the clinical adoption of any digital healthcare technology, evidence is required first, and their effects must be assessed before integrating them into healthcare systems such as Electronic Health Records (EHRs). The broad definition of digital health encompasses fields like wearable technology, telehealth and telemedicine, personalized medicine, the Internet of Things (Internet of things (IoT)), virtual reality (VR), Artificial Intelligence (AI), and mobile health (mHealth). Pharmaceutical digitalization is still in a testing phase regarding offering advanced administrations beyond conventional products. In this paper, digitalization from the perspective of diverse case studies was carried out to collect data from several companies, and a literature study was conducted to complement the data on healthcare development. The digitalization of health care is a game changer for developing health care.